Lehman Brothers : the fall from grace - Oji, Chijioke; Bowen, Amanda; Makin, Viola, 1952- ([London] : SAGE, 2016)
In September 2008, Lehman Brothers Holdings Inc. filed for bankruptcy protection at the United States Bankruptcy Court in Manhattan, New York. The news of Lehman's bankruptcy filing sent shockwaves through US financial markets and the impact was later felt across the world, contributing to the global financial crisis in the same year. This book studies the decline of an institution once looked upon as 'too big to fail'.
Originally Published in: Oji, C., Bowen, A., & Makin, V. (2013). Lehman Brothers: The Fall from Grace.WBS-2013-01. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; Lehman Brothers (1993-2008); electronic books; Global Financial Crisis, 2008-2009 -- Case studies; Bank failures -- United States -- History -- 21st century -- Case studies; Bankruptcy -- United States -- Cases